Who Educates and protects in order to guarantee the rights of children and adolescents: school interaction and the protection network - Lahr, Talita Bueno Salati [UNESP]; Castro-Carrasco, Pablo Javier; Oliveira, Vitoria Hellen Holanda [UNESP] (Unesp-faculdade Ciencias & Letras, 2022)
This research is part of a set of investigations conducted during the pandemic of COVID-19 and has as its problem the following question: Is there a difference between the perception of the protection network and the adults in the school (managers and teachers) about the interventions made by the school regarding conflicts involving aggression and disobedience to the rules by adolescents? To answer this question, we have as a general objective to verify the perception of teachers, managers, and other members of the protection network about the interventions made by the school regarding conflicts that involve aggression and disobedience to rules by adolescents. As specific objectives we aimed to verify if there are differences between the perception of adults who work in schools and other members of the protection network, and to verify if there are differences between the perception of teachers and managers about these interventions made by the school. Participating in the investigation were managers, teachers, and other actors in the protection network from different agencies, such as the Guardianship Council, Public Ministry, Social Assistance, and Health. We found a difference in perception between those who work at school and those who work in other organs of the protection network in relation to referrals to coexistence problems, with the school's actions being based on punitive sanctions, reinforcing the importance of training processes with the professionals of the school institution and articulation actions among all actors of the protection network.
Keywords: School; Protection network; Coexistence; Children; Adolescents